Vibro-acoustic behaviour of polymer-based composite materials produced with rice husk and recycled rubber granules. (20th December 2020) - Marques, Beatriz; António, Julieta; Almeida, João; Tadeu, António; de Brito, Jorge; Dias, Sara; Pedro, Filipe; Sena, João Dinis
Highlights: Development of innovative composites with RH and recycled rubber granules. Increasing the board's density and RH content improves compressive behaviour. Vibration isolation capacity depends on thickness, density and rubber content. All composites exhibit great potential for impact sound insulation. Abstract: This research concerns the study of composite boards made from polymer-based materials that include rice husk and recycled rubber granules, to see if they can mitigate vibrations and improve the impact sound insulation of floor solutions in buildings. The influence of the composite mix, mass density and board thickness on the overall performance was studied experimentally. First, the composites were studied under static compressive loading. Then, the behaviour under dynamic loads was evaluated through transmissibility tests for frequencies ranging from 20 to 200 Hz with five different static loading scenarios, from which the dynamic transfer stiffness and transmissibility curves were determined. The ability of the proposed composite boards to improve the impact sound insulation of floors was also assessed experimentally, in adjacent vertical acoustic chambers. The composite boards were tested as the top layer of the system and as part of a floating floor. For the latter, a thin slab was built above the tested specimen. The results indicate that composites produced from rice husk and recycled rubber granules can help to mitigate vibration in building solutions. Thicker samples whose rubber content was higher and apparent density lower showed higher vibration isolation capacity for a wide range of frequencies. Moreover, it was found that rice husk and rubber boards were able to improve the impact sound insulation of floor solutions. Composite boards with higher rubber content were found to perform better as floor coatings.